NOTES ON THE BIOLOGY OF TARPON, Tarpon atlanticus (CUVIER & VALENCIENNES), FROM COASTAL WATEERS OF CEARÁ STATE, BRAZIL - Ferreira de Menezes, Mariana; Paiva, Melquíades Pinto (Arquivos de Ciências do Mar)
-